Resilience of terrestrial mammals to logging in an active concession in Sarawak, Borneo - Maiwald, Marius Joscha; Mohd-Azlan, Jayasilan; Brodie, Jedediah F. (De Gruyter, 2021)
Selective logging is very widespread across the tropics and can alter the habitat for myriad wildlife species. But while many studies have assessed the impacts of past logging on forest animals, far fewer have investigated how species respond to logging while the timber operations are actually going on. This is an important knowledge gap because, considering the prevalence of logging across the world, numerous areas will be undergoing active extraction at any given time. We compared the occurrence and diel activity patterns of individual species of medium- to large-bodied terrestrial mammals, as well as the richness of the entire assemblage, among sites that were either unlogged, had been logged historically, or had ongoing ‘reduced impact’ timber extraction in the Kapit Region of Sarawak, Malaysian Borneo. We found no significant differences in estimated occupancy or activity patterns of particular species, or in overall species richness, among logging treatments. Across sites, species richness in this area appeared to be as high as or higher than in many other parts of the state, including some protected areas. Though monitoring is needed to assess potential long-term impacts, our results suggest that reduced-impact logging could allow economic development that is sustainable for many wildlife populations.